ANALISIS KUALITAS LAYANAN MOBILE JKN MENGGUNAKAN METODE E-SERVICE QUALITY, CUSTOMER SATISFACTION INDEX (CSI) DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - SAPUTRA, HADI; ISTIQOMAH, RINITA (Jurnal Jaminan Kesehatan Nasional, 2024)
Mobile JKN is an application facilitating remote access to services under the national health insurance program managed by BPJS Kesehatan, offering numerous features for participant convenience. As of June 2023, registrations in the Surakarta area reached 92,101. This study evaluates the service quality of the Mobile JKN application using e-service quality, Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA) methodologies. A quantitative approach focused on 100 participants visiting the Surakarta BPJS Kesehatan branch. The results of this research are that participants who use the Mobile JKN application are satisfied with the Mobile JKN application service, with an average gap value of 0.06 (positive value), and a CSI value of 81.4%, which indicates that participants are satisfied with the Mobile JKN service. IPA results identified three indicators as top priorities for further enhancement and quality improvement.